Pengaruh Pemberian William Flexion Exercise Terhadap LBP Miogenik Pada Karyawan Kantor Pusat PT. Nusantara Medika Utama - Achmad Sidarto; Agung Hadi Endaryanto; Dian Pitaloka Priasmoro; Achmad Abdullah (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: to identify The purpose of this study was to determine the effect of william Flexion on pain reduction in myogenic LBP in workers at PT NMU.Methods: This article  This research is an experimental study used One Group Pretest and Posttest. The One Group Pretest and Posttest method was chosen because only one group was taken as the research subject without being compared to other groups. In this study, the research subject group was given william flexion exercise therapy in the clinical treatment room of PT NMU. The implementation of this research was carried out from August 2021 to September 2021. The population of this study was all 50 employees of PT NMU. Population samples taken were patients who met the inclusion and exclusion criteria. Inclusion criteria included employees who experienced low back pain prior to the study of at least mild and moderate degrees and did not take painkillers. Exclusion criteria included patients with chronic LBP (>3 months) and employees whpo experienced low back pain due to other diseases and had been diagnosed. The population of this study were 30 patients with complaints of LBP at PT NMU.Results:  Research that has been conducted on 30 respondents who experienced low back pain myogenic in employees at the Head Office of PT. Nusantara Medika Utama Mojokerto,Conclusion: Terdapat pengaruh pemberian  William Flexion Exercise terhadap penurunan nyeri pada pasien Low Back Pain Myogenic pada karyawan di kantor pusat PT. Nusantara Medika Utama, Mojokerto.